Chapter 4: Latin American Cyberprotest: Before and After the Zapatistas. - Pitman, Thea (Latin American Cyberculture & Cyberliterature, 2007)
Chapter 4 of the book "Latin American Cyberculture and Cyberliterature," edited by Thea Pitman and Claire Taylor is presented. The author argues that grassroots and activist organizations in Latin America have contrived to make strategic use of the Internet for pro-democratic networking and awareness activities since 1980s. It explores a range of confusing neologisms used to define the conjunction of the Internet with various activities from the non-violent expression of alternative political ideas.